Experiential Learning Model Based on Local Wisdom in Learning Islamic Cultural History - Agus Purwowidodo (Al-Hayat: Journal of Islamic Education, 2024)
This study examines how the local wisdom-based experiential learning model influences the improvement of metacognitive skills, learning motivation, and learning outcomes in the subject of Islamic Cultural History (SKI) in grade V students of State Madrasah Ibtidaiyah (MI), who previously used more memorisation-based and less contextual learning methods. This study uses a quantitative method with a pretest-posttest experimental design. Data collection through tests, questionnaires, and observations on elementary school students in Tulungagung Regency. Statistical tests using MANOVA and SPSS-26.0. The results of the study showed that the application of experiential learning based on local wisdom was significantly more effective in improving students' understanding of the efforts of the Prophet Muhammad SAW, as well as SKI learning outcomes and metacognitive skills compared to the expository method. This model also succeeded in increasing students' learning motivation and developing independent learning and intercultural skills. In addition, experiential learning plays an important role in preparing students to face global challenges. The average learning outcomes of students taught with the experiential model were higher than the expository method, namely 87.54 compared to 72.72. This study has limitations in the generalization of findings. The originality of this study lies in the experiential learning model based on local wisdom that is effective in improving students' understanding, motivation, and metacognitive skills. The implications of this study for the development of more adaptive curriculum and teaching strategies and preparing students to face global challenges.